KOMUNIKASI INTERPERSONAL DALAM MENGINTERNALISASIKAN NILAI CATUR BHAKTI KEPADA SISWA PERSAUDARAAN SETIA HATI TERATE (Studi Kasus Pada Ranting Baradatu Cabang Waykanan) - tri my indah; Noning Verawati; Budhi Waskito (KONTEKSTUAL : Jurnal Ilmu Komunikasi, 2026)
Tri My Indah. Interpersonal Communication In Internalizing The Values Of Catur Bhakti To Students Of Persaudaraan Setia Hati Terate (Case Study at Baradatu Branch, Waykanan). Supervised by NONING VERAWATI, M.A             This study is motivated by the importance of instilling Catur Bhakti values in students of the Persaudaraan Setia Hati Terate (PSHT) Baradatu Branch (Way Kanan Chapter) as a means of character building amidst the decline in discipline, responsibility, and respect for moral values among adolescents. The study aims to examine the forms of interpersonal communication employed by trainers, the communication interaction process between trainers and students, and the design and planning of communication used to instill Catur Bhakti values. A qualitative approach using a case study method was adopted. Informants included the Branch Chairperson (key informant), trainers and students (primary informants), and parents (supporting informants), all selected via purposive sampling. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. Data validity was verified through source and technique triangulation. The results indicate that trainers' interpersonal communication is characterized by openness, empathy, supportiveness, a positive attitude, equality, and active listening. Communication occurs as a two-way process within small groups (rayon), involving the delivery of advice, leading by example, dialogue, evaluation, motivation, and persuasive approaches tailored to individual student characteristics. The study also found that communication design was previously situational; consequently, the researcher formulated a more structured communication plan involving the development of Standard Operating Procedures (SOPs) for trainer communication, periodic evaluations, and strengthened collaboration with parents. It is concluded that open, persuasive, and planned interpersonal communication plays a crucial role in the successful internalization of Catur Bhakti values among PSHT students. Keywords: Catur Bhakti, Interpersonal Communication, Value Instillation, Persaudaraan, Case Study